Maternal monocytes in pregnancy and preeclampsia in humans and in rats. (February 2017) - Faas, M.M.; de Vos, P.
Highlights: Monocyte activation and maturation was observed in pregnancy. Further monocyte activation and maturation was observed in preeclampsia. During rat pregnancy, similar changes occur in monocytes as during human pregnancy. In rat models for preeclampsia, similar changes in monocytes occur as during human preeclampsia. The rat is a useful model to study monocyte changes in pregnancy and experimental preeclampsia. Abstract: Monocytes are short-lived cells, arising from the bone marrow and maturing in the circulation. They play an important role in immune responses and are thought to be important for healthy pregnancy. In humans, 3 subpopulations of monocytes have been identified: classical, intermediate and non-classical monocytes. These subpopulations have different functions and phenotypical characteristics. Healthy pregnancy is characterized by a pro-inflammatory condition, with increased numbers of monocytes and monocyte activation as well as with increased numbers of intermediate monocytes and decreased numbers of classical monocytes. This may suggest monocyte maturation. Preeclampsia is an important pregnancy complication characterized by hypertension and proteinuria developing in the second half of pregnancy. The pathophysiology of preeclampsia is associated with further activation of the inflammatory response, further activation of monocytes and further monocyte maturation. In the present review we focus on the role of monocyte activation and maturation in healthy and preeclamptic pregnancy.